Analisis Peramalan Kebutuhan dan Safety Stock Material Plat Dalam Pembuatan Kapal Pada PT. XYZ Menggunakan Metode Time Series - Ahyaliya, Marsya Laila; Tranggono (Jurnal Serambi Engineering, 2025)
A shipyard is an industry that designs, builds and repairs ships. The shipbuilding process at a shipyard involves a number of complex stages, from design to launch. If there is too much stock, the company will incur high storage costs. Conversely, if the stock is too low, the production process will be hampered by delays in material delivery, which can ultimately affect the ship's launch schedule. To overcome these problems, PT XYZ needs to implement a better inventory control system. This system aims to ensure the availability of sufficient plate materials to meet production requirements, including forecasting demand, determining safety stock levels and setting reorder points. The method used in this study is a time series consisting of three methods, namely single moving average, weighted moving average and single exponential smoothing using POM-QM software. Based on the results of the study, the feasible method to be applied to PT XYZ forecasting is a moving average with a MAD value of 5,444, MSE of 46,679, MAPE of 6,695% and forecasting results of 85 pcs per month. Based on the calculation results, it is recommended to reorder the sheet material when the stock reaches the reorder point of 271 pcs. This figure takes into account the safety stock of 18 pcs.